Modeling of turbulent natural convection based on a two-fluid approach - Malikov, Zafar Mamatkulovich; Navruzov, Dilshod Primkulovich (Computational Continuum Mechanics, 2024)
The paper provides mathematical modeling of turbulent natural air convection at a heated vertical plate based on a fairly recently developed two-liquid turbulence model. The considered problem, despite its relative simplicity, contains all the main elements characteristic of the currents near the wall due to buoyancy forces. A significant disadvantage of the RANS turbulence models used to solve such problems is that for their numerical implementation it is necessary to set the laminar-to-turbulent transition point, which must be determined experimentally. Thus, all RANS models are unable to describe a laminar-to-turbulent transition zone. Therefore, the main purpose of the work is to test the ability of the two-liquid turbulence model to describe the transition zone. Well-known publications have shown that the two-liquid model has high accuracy and stability, and is also able to adequately describe anisotropic turbulence. The turbulence model used in this work is supplemented with an additional thermal force, which can be ignored in many flows with forced convection. However, in the natural convection currents, it is this force that contributes to the transition of the flow regime. To validate the model, as well as to verify the computational procedure, the numerical results obtained are compared with the results of the well-known RANS turbulence models (the one-parameter Spalart-Allmaras (SA) model and the Reynolds stress transfer (RSM) model), as well as with the available experimental data. It is shown that the two-liquid model adequately reproduces the laminar-to-turbulent transition zone, and the numerical results obtained are in good agreement with experimental data.
Keywords: two-fluid approach to turbulence; heated vertical plate; verification; natural convection; thermal force; Nusselt number; transition zone